PTH-015 Safety and utility of endoscopic retrograde cholangio-pancreatography (ercp) in children and adolescents performed by adult gastroenterologists– a tertiary care hospital experience. (22nd June 2015) - Saleem, R; Raja, O; Latif, L; Ollerton, A; Harrison, P; Devlin, J
Abstract : Introduction: Endoscopic retrograde cholangio-pancreatography (ERCP) is a technically demanding endoscopic procedure and is not widely performed in children. Limited data is available on safety and usefulness of this procedure in children. At many institutions, paediatric ERCP is performed by adult gastroenterologists not formally trained in paediatric gastroenterology. The aim of this study was to evaluate the safety and efficacy of ERCP in children and adolescents with pancreaticobiliary diseases performed by adult gastroenterologists in a single tertiary care centre. Method: We conducted a retrospective review on the data of all paediatric patients aged <18 years who had undergone an ERCP between Jan 2009 and Dec 2013 at King's College Hospital, London, UK. Patient's demographics, procedural indications, outcomes, interventions, technical success and complications rates were evaluated. All procedures were performed under general anaesthesia. Results: One hundred and eighty procedures were performed on 112 patients. 58 (52%) were girls, and mean age was 10.2 years (range, 1 week–18 years). Most frequent indications for ERCP were: cholestatic jaundice with abnormal imaging (n = 55), choledocholithiasis (n = 29), pancreatitis (n = 19), biliary/pancreatic duct stricture (n = 18), bile leak (n = 14) and pancreatic duct trauma (n = 9). Successful biliary cannulation was achieved in 94% (170) cases. ERCP findings were: bile duct strictures 40 (23%), bile duct stone (s) 26 (15%), choledochal anomaly 15 (8.8%), pancreatic duct strictures 10 (6%), biliary atresia 10 (6%), pancreatic divisum 8 (4.7%) and pancreatic duct stone (s) in 5 (3%) patients. Therapeutic interventions performed included biliary sphinterotomy (n = 21), precut sphinterotomy (n = 4), pancreatic sphincterotomy (n = 3), biliary stenting (n = 47), pancreatic duct stent placement (n = 25) and balloon dilation of stricture (n = 18). 30 (16.6%) cases were complicated with post-ERCP pancreatitis (PEP). Mild bleeding occurred in 5(2.7%) cases and none of them required blood transfusion. There was only one case of duodenal perforation following pre-cut sphincterotomy which was managed conservatively. There were no deaths reported within 30 days of the procedure Conclusion: Overall ERCP in children and adolescents is a safe and reliable procedure and should be safely performed by adult gastroenterologists well-trained in advanced endoscopy. Disclosure of interest: None Declared.